Anti-NMDA receptor encephalitis: a case study and illness overview - Brian Ford; Alex McDonald; Shilpa Srinivasan (BioExcel Publishing Ltd, 2019)
Anti-N-methyl D-aspartate (NMDA) receptor (anti-NMDAR) encephalitis is among one of the most common autoimmune encephalitides. However, variations in clinical presentation and nonsequential multiphasic course often lead to delays in diagnosis. The mild encephalitis (ME) hypothesis suggests a pathogenetic mechanism of low-level neuroinflammation sharing symptom overlap between anti-NMDAR encephalitis and other psychiatric disorders including schizophrenia. Clinical symptoms of anti-NMDAR encephalitis may mimic schizophrenia and psychotic spectrum disorders or substanceinduced psychosis. Although initially described in association with ovarian teratomas in women, anti-NMDAR encephalitis has been reported in individuals without paraneoplastic association, as well as in males. It can affect all age groups but is usually lower in prevalence in individuals greater than 50 years old, and it affects females more than males. Clinical evaluation is supported by laboratory workup, which includes cerebrospinal fluid (CSF) assays. The latter often reveals lymphocytic pleocytosis or oligoclonal bands with normal to elevated CSF protein. CSF testing for anti-NMDAR antibodies facilitates diagnostic confirmation. Serum anti-NMDAR antibody assays are not as sensitive as CSF assays. Management includes symptomatic treatment and immunotherapy.